2020
DOI: 10.4102/safp.v62i1.5108
|View full text |Cite
|
Sign up to set email alerts
|

Perceived enablers of exclusive breastfeeding by teenage mothers in Ghana

Abstract: Background: Exclusive breastfeeding for the first 6 months can prevent diseases, boost immunity and improve quality of lives of infants. Ghana implemented programmes aimed at reaching the global target of increasing exclusive breastfeeding for the first 6 months to at least 50% by the year 2025. The country witnessed a decline in the overall rate of exclusive breastfeeding and an increase in the number of teenage mothers. Globally, teenage mothers are less likely to breastfeed than mothers of other age groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Building on previous studies that recommend strengthening the knowledge base of health workers and mothers to support awareness of breastfeeding benefits throughout prenatal to postpartum periods [ 24 27 ], our study highlights gaps in knowledge on the management of women and neonates that have challenges to breastfeeding and explains the low scores in such neonates. These gaps have been reported earlier among primiparous women [ 28 ] teenage mothers [ 29 ] skills in expressing milk, management of breast engorgement, and painful and cracked nipples [ 30 ]. Updating the current breastfeeding training manuals with problem-based training for healthcare workers and mothers addressing the specific problematic issues would be a step towards strengthening breastfeeding practices.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Building on previous studies that recommend strengthening the knowledge base of health workers and mothers to support awareness of breastfeeding benefits throughout prenatal to postpartum periods [ 24 27 ], our study highlights gaps in knowledge on the management of women and neonates that have challenges to breastfeeding and explains the low scores in such neonates. These gaps have been reported earlier among primiparous women [ 28 ] teenage mothers [ 29 ] skills in expressing milk, management of breast engorgement, and painful and cracked nipples [ 30 ]. Updating the current breastfeeding training manuals with problem-based training for healthcare workers and mothers addressing the specific problematic issues would be a step towards strengthening breastfeeding practices.…”
Section: Discussionmentioning
confidence: 77%
“…This has been advocated previously by other researchers. An earlier Malawian study showed that men had low levels of knowledge on breastfeeding despite being influential household decision-makers [ 34 ] and a Ghanaian study found that partner supporter was an enabler to breastfeeding [ 29 ]. Our findings of grandmothers and aunts sometimes being a barrier to breastfeeding resonates with a Ghanaian study that reported mothers not being allowed to breastfeed especially at night because influential relatives, such as grandmothers, would not allow them [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have established that antenatal clinics provide an opportunity for health care workers (midwives, community health nurses) to interact and educate mothers on infant feeding, the nutritional value of EBF, and challenges associated with EBF. The health education provided by health care workers during antenatal care visits increases knowledge on infant feeding and thus, enhances the practice of exclusive breastfeeding [ 52 – 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…People commonly rely on health care workers information and actions to guide their decision. For instance, studies have shown that health care workers counselling on exclusive breastfeeding and complementary feeding influence the practice of exclusive breastfeeding among mothers [22,23]. Against this backdrop, this study sought to assess and identify the determinants of COVID-19 acceptability among health care workers in Ghana.…”
Section: Introductionmentioning
confidence: 99%